Appendix for: A proposed solution to a urological tightrope walk: The challenge of transition of spina bifida patients from pediatric to adult care in Ontario - Koyle, Martin A.; Golda, Nicole; Hillis, Christopher; Oldershaw, Betty; DeMelo, Margaret; Uyeno, Jennifer (Canadian Urological Association Journal, 2016)
N/A